Out of the blues [compact disc] - Scaggs, Boz, 1944- (Concord Records, 2018)
The self-produced 2018 release finds Boz Scaggs utilizing his iconic voice and guitar skills to a set of classics and four originals. The legendary singer-songwriter and guitarist gathered an all-star studio band.